PROTECTIVE ACTION OF PERGULARIA DAEMIA AND TERMINALIA CATAPPA ON CCL4 INDUCED HEPATOTOXICITY IN ALBINO RATS - VIJAYA PACKIRISAMY,; VIJAYALAKSHMI.K, (International Journal of Pharma and Bio Sciences, 2016)
To investigate the hepatoprotective activity of the hydroalcoholic extracts of Pergularia daemia and Terminalia catappa on CCl4 induced hepatotoxicity in wistar albino rats. The animals were grouped into seven with six rats in each group. Group I served as vehicle control, Group II served as Hepatotoxin treated group: (30% of CCl4 - 1ml/kg,i.p.). Group III served as drug control :(30% of CCl4 1ml/kg ,i.p.) + (Silymarin- 25 mg/kg,,p.o.). Group IV,V served as pre treatment groups: HAEPD(200 mg/kg ,p.o.)+30% CCl4 and HAETC (200 mg/kg ,p.o.)+ 30% CCl4. Group VI,VII served as Post-treatment groups: 30%CCl4 + HAEPD and 30%CCl4 +HAETC (200 mg/kg,p.o.) for the period of twenty five days. The biochemical parameters such as cholesterol,triglycerides, LDL,VLDL, Clotting time, urea ,uricacid, bilirubin creatinine were significantly increased (p<0.001) in group II animals. But the Pre and Post treatment with hydroalcohol extracts of Pergularia daemia and Terminalia catappa (200 mg /kg,p.o.) showed reduction of cholesterol , triglycerides ,LDL,VLDL,Clotting time, urea ,bilirubin creatinine and increased the levels of RBC, Hb,PCV,HDL and protein profile. From this results it can be conclude that the groups treated with HAEPD and HAETC showed hepatoprotective effects against CCl4 induced liver damage in rats.